Prevalence of Proteinuria and Albuminuria in an Obese Population and Associated Risk Factors - Rosenstock, Jordan L.; Pommier, Max; Stoffels, Guillaume; Patel, Satyam; Michelis, Michael F. (Frontiers in Medicine, 2018)
Obesity has been increasingly recognized as a risk factor for kidney disease and both proteinuria and microalbuminuria have been associated with obesity. The actual prevalence of microalbuminuria and proteinuria in obese patients in the United States (US) has not been clearly described in the literature. Furthermore, obesity is associated with risk factors of kidney disease, such as diabetes and hypertension (HTN), and the prevalence of proteinuria and albuminuria excluding these risk factors is uncertain. In this study, we collected urine albumin/creatinine and urine protein/creatinine ratios on obese patients undergoing bariatric surgery to determine the prevalence of albuminuria and proteinuria in obese patients with and without associated diabetes and HTN. The study included 218 obese patients undergoing bariatric surgery at a New York City hospital. The mean age was 42.1 ± 11.3 years. The mean body mass index (BMI) was 43.9 ± 8.1. Diabetes (DM) was present in 25%. HTN was present in 47%. The prevalence of proteinuria and albuminuria was 21% (95% CI: 15.8–27.1%) and 19.7% (95% CI: 14.2–26.2%) respectively. Among those without DM but who had HTN, 22.6% (95% CI: 12.9–35) had proteinuria and 17% (95% CI 8.4–30.9) had albuminuria. Of patients with neither DM nor HTN, 13.3% (95% CI: 7.3–21.6) and 11% (95% CI: 5–17%) had proteinuria and albuminuria, respectively. Diabetics had a significantly higher prevalence of proteinuria and albuminuria than the non-diabetic groups. The non-diabetic groups did not differ significantly from each other in terms of prevalence of proteinuria and albuminuria. The BMI for diabetics did not differ from non-diabetics. On multivariate analysis, only the presence of diabetes was associated with proteinuria and albuminuria. BMI, age, and HTN were not predictive. In conclusion, we found a relatively high prevalence of microalbuminuria and proteinuria in an urban, US, obese population undergoing bariatric surgery. When diabetics were excluded, there was a lower prevalence. Even patients who had neither diabetes nor HTN, still, however, had much greater amounts than seen in the general US population, likely reflecting an adverse effect of obesity itself on renal physiology.